An International Human Rights Law Perspective on The Impact of Digitalization on The Alevi Community - Erol, Melih Uğraş (Journal of Alevism-Bektashism Studies, 2023)
The digitalization of law is occurring at an accelerated pace due to advancements in technology and the influence of the internet. This digitalization has brought about a significant transformation in the acquisition and diffusion of legal information and instruments, presenting both benefits and obstacles, particularly in the field of international human rights law. Comprehending the impact of digitalization on human rights is of utmost importance for populations such as the Alevis in Turkey, who are currently enduring violations of their fundamental rights. This is because technological advancements and their implications for human rights law play a vital role in ensuring the safeguarding and implementation of human rights while also potentially enabling tangible breaches of these rights. The European Court of Human Rights has often ruled in favor of Alevis in cases involving human rights breaches. However, the advent of digitalization brings up a new realm for Alevis’ human rights issues, since they may face distinct challenges arising from the digitalization of human rights. There are advantages to the digitalization of human rights law for Alevis, particularly in terms of enhanced accessibility to legal materials, while also having disadvantages, e.g., online hate speeches and low digital literacy, and facing potential obstacles such as bias in artificial intelligence (AI) systems. Digital platforms are also significant in safeguarding Alevi cultural rights and enabling the establishment of an understanding of being a community among Alevis via the use of internet platforms. In the era of digitalization of law, while Alevis comprehend their human rights and freedoms, they also use online platforms for activism. This article offers a thorough examination of the consequences of the digitalization of international human rights law for the Alevi population. It specifically focuses on the advantages and disadvantages associated with this phenomenon.
Keywords: Digitalization; Alevis; Human Rights Law; Turkey